P100 Characteristics of real world fibroscans in the diagnosis of NASH. (19th June 2022) - Tummala, Siri; Fernandes, Christopher; Smith, Brooklin; Hungerman, Miranda; Hodnick, Brooke; Ritter, Tim
Abstract : Introduction: Non-alcoholic steatohepatitis (NASH) is an aggressive form of nonalcoholic fatty liver disease (NAFLD) characterized by inflammation and progressive fibrosis. Optimal diagnosis is traditionally achieved with liver biopsy, but this is invasive, costly, has potential complications, and both inter and intra-observer variability. Further patients are often reluctant to follow through with liver biopsy due to these issues. Fibroscan is liver ultrasonographic elastography used to stage liver fibrosis that is a rapid test and also noninvasive, painless, and less costly than a liver biopsy. Fibroscans are increasingly being used in lieu of liver biopsies. In this study we report real world data on the experience with fibroscans in a large gastroenterology practice. The aim of this study is to assess the distribution of fibroscan results in this cohort and to compare available fibroscan results with liver biopsies. Methods: We conducted a retrospective analysis of patients suspected of having NASH from November 2020 to November 2021 at a large Texas gastroenterology private practice. All patients with a fibroscan were included and sub-analyzed with those who also had a liver biopsy. Data collection comprised of BMI, fibrosis scores, kilopascals (kPa) scores, and liver biopsy results. Indications for suspected NASH included elevated transaminases, abnormal abdominal imaging and obesity (BMI >30) with associated diabetes. Results: There were 559 patients who underwent a fibroscan for the evaluation of NASH. The majority of patients had a BMI of >30 (334 patients, 60%), a kPa of <8.2 (383 patients, 69%), a CAP score >292 (281 patients, 50%), and a Fib4 <1.45 (281 patients, 50%). Patients who were screened by fibroscan and found to be at a low risk of fibrosis did not undergo the risk or expense of further evaluation of a liver biopsy. of the total cohort of 559, only 57 (10%) met this criteria and had liver biopsies performed in addition to the fibroscan. of these, 46 (81%) of biopsies reported the same fibrosis results predicted by fibroscans, 4 (7%) indicated at least 2 stages of fibrosis below that predicted by fibroscans, and 7 (12%) denoted at least 2 stages more fibrosis than predicted by fibroscans. Conclusion: Fibroscan is a valuable tool in assessing patients with NASH and offers a rapid, noninvasive, cost-effective test to confirm disease. We observed comparable results between fibroscan and liver biopsy results. This study suggests that fibroscans can be a viable alternative to liver biopsies in the diagnosis of NASH in a private practice setting. Additional evaluations can confirm these preliminary findings.